Case report: Suspected propofol associated Heinz body anemia in five mechanically ventilated dogs: a historical case series - Ireland, Emily M.; Sharp, Claire R.; Leister, Ellie M.; Boyd, Susan (Frontiers in Veterinary Science, 2025)
ObjectiveThe aim of this report is to raise awareness of the risk of oxidant-induced erythrocyte injury, including Heinz body (HB) anemia, in critically ill dogs by describing the condition in five dogs receiving constant rate infusions of propofol.Case summaryThis case series describes five dogs with suspected propofol-induced HB anemia undergoing mechanical ventilation (MV) for lower motor neuron disease. Four of the five dogs were treated for tick paralysis (Ixodes holocyclus) and one was treated for suspected eastern brown snake (Pseudonaja textilis) envenomation. Propofol constant rate infusions were administered as part of total intravenous anesthesia. All five dogs became anemic, and a complete blood count and blood smear interpretation by a specialist clinical pathologist confirmed the presence of oxidative red blood cell injury (eccentrocytosis and HBs). The duration of MV ranged from 76 to 131 h, with HBs identified within 47–96 h of commencing propofol. All five dogs survived to discharge, with one dog requiring a blood transfusion.DiscussionWhile propofol-induced HB anemia is a recognized phenomenon in cats, to the author’s knowledge, this is the first case series detailing multiple occurrences in dogs. Veterinarians should be aware of the risk of propofol-induced oxidative erythrocyte injury in dogs receiving prolonged infusions of propofol, and consider risk mitigation by using propofol as part of multiagent intravenous anesthesia, keeping dose rates as low as possible, and daily monitoring of blood smears and red blood cell indices.